2006
DOI: 10.1037/0022-3514.91.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the dopaminergic basis of extraversion in humans: A multilevel approach.

Abstract: A recent theory suggests that the agency facet of Extraversion (E) is based on brain dopamine (DA). The paucity of human data relevant to this model is probably due to the lack of widely accessible noninvasive psychophysiological indices and well-established behavioral measures sensitive to both E and manipulations of DA activity. Aiming to identify such measures, the authors assessed the electroencephalogram and n-back task performance in groups of introverts and extraverts after administration of either plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
8

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 77 publications
13
143
8
Order By: Relevance
“…In an initial test of this hypothesis, we indeed found not only that a simple index of resting posterior minus anterior EEG theta activity specifically correlated with trait aE, but also that this association was completely reversed after administration of the selective dopamine D2/D3 receptor antagonist sulpiride, supporting an association of this novel index with the presumed neurochemical basis of aE (Wacker et al, 2006). Meanwhile, we consistently observed a correlation between aE and posterior minus anterior EEG theta activity in six independent studies (total N > 1,500), collected in three different laboratories (Koehler et al, 2010;Wacker & Gatt, 2010).…”
Section: Agentic Extraversion and Posterior Versus Anterior Eeg Thetamentioning
confidence: 83%
See 2 more Smart Citations
“…In an initial test of this hypothesis, we indeed found not only that a simple index of resting posterior minus anterior EEG theta activity specifically correlated with trait aE, but also that this association was completely reversed after administration of the selective dopamine D2/D3 receptor antagonist sulpiride, supporting an association of this novel index with the presumed neurochemical basis of aE (Wacker et al, 2006). Meanwhile, we consistently observed a correlation between aE and posterior minus anterior EEG theta activity in six independent studies (total N > 1,500), collected in three different laboratories (Koehler et al, 2010;Wacker & Gatt, 2010).…”
Section: Agentic Extraversion and Posterior Versus Anterior Eeg Thetamentioning
confidence: 83%
“…Because the mental processes associated with the two types of theta rhythm are, at least in part, mutually exclusive, the activity in brain sources of frontal midline and parietal midline theta should also be reciprocally related. Thus, we proposed that the difference between frontal and parietal midline theta activity could capture a meaningful aspect of EEG theta activity in a single measure (Wacker, Chavanon, & Stemmler, 2006).…”
Section: Agentic Extraversion and Posterior Versus Anterior Eeg Thetamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that individual differences in extraversion evolve from differences in the functioning of dopaminergic systems (Depue & Collins, 1999). For example, extraversion was strongly correlated with changes in working memory (WM) performance using the n-back task, thought to be influenced by dopamine activity, following a dopamine agonist (Wacker, Chavanon, & Stemmler, 2006). Extraversion also correlated with reaction to a dopamine agonist, as measured by spontaneous eyeblink response (Depue, Luciana, Arbisi, Collins, & Leon, 1994).…”
Section: Ab Taskmentioning
confidence: 93%
“…Prior research showing that people high in extraversion had more amygdala activity to happy faces may be reflecting enhanced amygdala response to the socially rewarding or novelty components of extraversion (Canli et al, 2002). Furthermore, people with high extraversion may respond more to reward incentives used to motivate behavior (Depue & Collins, 1999) especially in challenging circumstances (Lieberman & Rosenthal, 2001;Wacker, Chavanon, & Stemmler, 2006). Thus extraversion might be more related to operant conditioning rather than a classical conditioning paradigm, where rewards are not contingent on behavior, such our paradigm.…”
Section: Influence Of Personality On Observational Learningmentioning
confidence: 94%